(untitled) (Heritage, 2022)
This paper presents empirical research findings with the aim to determine the knowledge and opinion of teachers on the representation of ethnic musical heritage of Kosovo and Metohija in the teaching process in the context of teaching music and physical education in the lower grades of primary schools in the north of Kosovo and Metohija. The survey was conducted on a sample of 73 teachers from the municipality of Leposavic and Kosovska Mitrovica in the course of 2019. The survey technique led to the results of this research. The subject of research is the empirical verification of the representation of popular music creativity of Kosovo and Metohija in the teaching process. The research is aimed at understanding the factors that influence the representation of national musical creativity of Kosovo and Metohija in teaching music and physical education in elementary grades. The survey results indicated that as very important contexts in solving problems of education of folk dances and songs through objects music culture and physical education an important place in the curriculum or folk dances and songs from Kosovo and Metohija, regardless of the value that they have not underrepresented in class music and physical education. The research indicated that teachers do not know enough basic music features of folk songs and dances from this region. On the other hand they are aware of the importance of applying these facilities in the preservation of national and cultural identity of the nation. The main reasons for this are, in the opinion of teachers, lack of relevant literature and teaching aids. It was concluded that teachers should be addressed to Ethnomusicology and musicapedagogical literature that can serve as a selection of materials suitable for processing school